Experimental investigation on the seismic isolation for a legged wine storage tank. (June 2017) - Colombo, J.I.; Almazán, J.L.
Abstract: Because of the booming of the winery industry in some seismic countries such as, the U.S, Italy, Chile and Argentina, the seismic protection of wine storage tanks may be of a practical importance. Previous numerical and theoretical investigations have shown that seismic isolation can reduce the seismic demand on liquid storage tanks compared to the fixed base case. However, there are not experimental works about the seismic performance and protection of legged wine storage tanks, nor practical applications, reported in the technical literature. Therefore, in this paper, the effectiveness of a novel seismic isolation system has been investigated by shaking table tests on a full-scale legged tank, typically used in the wine industry. A comparison of the seismic behaviour of fixed base and isolated base configurations is presented. Two alternative base isolation systems have been studied: flat sliding bearings with a central leg acting as restoring element, and flat sliding bearings without any restoring element. The restoring force of the central leg was performed by means of five compression springs. The experiments were carried out using 3 natural and 3 artificial records. Measurements were made of the shear and axial forces in one leg of the tank, and the horizontal displacement of the tank. The experiments showed the beneficial effects of using the proposed isolation system in legged wine storage tanks, reducing the shear and axial forces in comparison with the fixed base configuration and reducing the horizontal displacement compared to the flat sliding bearing configuration without any restoring element. Highlights: Shaking table test was conducted on a full-scale legged wine storage tank with and without seismic isolation. A novel seismic isolation system was proposed for legged wine storage tanks. Using seismic isolation may represent a significant improvement in the seismic reliability of legged wine storage tanks.